PERAN GOOGLE.INC DALAM MENGGAGALKAN SOPA ( STOP ONLINE PIRACY ACT ) OLEH AMERIKA SERIKAT ( 2011-2012 ) - Rafiqy, M. Haris; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses the role of Google Inc. in thwarting the legalization of SOPA ( Stop Online Piracy Act) by the US. Internet is a platform for the delivery of information between users, and the other side the internet is a very promising business especially with the rapid developments in technology and communications. Google Inc. is one company that uses cyber cyberspace as an business. Relevant with the free flow of information on the internet, two perspectives appears related to the internet, namely explorative and emancipatory. This has led to the illegal activities of Internet users, piracy activities. US sees this as a threat, so it appears the draft law policy SOPA (Stop Online Piracy Act). The rearch uses qualitative method according library system of study. The author is applying constructivism as perspective and propaganda theory of Harold Dwight Lasswell ini explain the Google’s propaganda to against SOPA what will be realease of US legislative. Constructivism emphasis the social character form by interest and identify actors. While propaganda is an attempt to forms, affect, alter, direct and control attitudes and opinions of the community in order to archieve a particular goal, by spreading idea of implanting and systematically into the minds of target. This research show that Google was followed by propaganda activity by using website blackout. Google uses Google Doodle in the search engine to attract the attention of Internet users around the world turn affects and escorted them to help support what is carried by Google.Inc. In its propaganda Google also makes a link that *Student of International Relation Faculty of Social and Political Science University of Riau takes into petitions that can be used by Internet users in the world to vote against SOPA rejection. Then Google's action also followed various other sites that participate in conducting activities and reject SOPA blackout promoted by the US Legislative. Keywords : Cybercpace, Congress, Piracy, Propaganda, SOPA, Internet user.